2015
DOI: 10.1021/acs.est.5b00074
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the Minamata Convention on Mercury Emissions and Global Deposition from Coal-Fired Power Generation in Asia

Abstract: ABSTRACT:We explore implications of the United Nations Minamata Convention on Mercury for emissions from Asian coal-fired power generation, and resulting changes to deposition worldwide by 2050. We use engineering analysis, document analysis, and interviews to construct plausible technology scenarios consistent with the Convention. We translate these scenarios into emissions projections for 2050, and use the GEOS-Chem model to calculate global mercury deposition. Where technology requirements in the Convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 61 publications
(147 reference statements)
1
65
0
3
Order By: Relevance
“…), but total Hg emissions over this period increased less (5.8% y −1 ) because of the implementation of FGD (21). This previously unaccounted shift in speciation implies greater declines in near-field Hg deposition than previously estimated.…”
Section: Revised Inventory Of Hg Emissionsmentioning
confidence: 68%
See 2 more Smart Citations
“…), but total Hg emissions over this period increased less (5.8% y −1 ) because of the implementation of FGD (21). This previously unaccounted shift in speciation implies greater declines in near-field Hg deposition than previously estimated.…”
Section: Revised Inventory Of Hg Emissionsmentioning
confidence: 68%
“…Recent work suggests weaker growth in Chinese emissions than previously estimated because of improved data on new coal-fired utilities with flue gas desulfurization (FGD) (20,21). Also, the increasing trend in ASGM emissions appears to be a spurious effect of improved reporting (9).…”
Section: Revised Inventory Of Hg Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest sources of anthropogenic mercury emission are stationary coal combustion, artisanal and small-scale gold mining, and metals production (18). Under NP, emissions are projected to more than double, largely as a result of growth in coal use in Asia (19); thus, the main differences in policy and NP projections depend on assumptions about emission controls for coal (20). Air quality abatement technologies such as flue gas desulfurization can capture mercury as a cobenefit.…”
Section: Resultsmentioning
confidence: 99%
“…Projections suggested that they would continue to be the leading emitters. Given the substantial emissions from these two countries alone, cooperation from both China and India was essential to addressing mercury globally (Giang et al 2015).…”
Section: India's and China's Positions In The Mercury Negotiationsmentioning
confidence: 99%